Iridium-catalyzed intramolecular CN and CO/S cross-coupling reactions: Preparation of benzoazole derivatives. Issue 40 (3rd October 2019) - Shi, Yajie; Zhou, Qifan; Du, Fangyu; Fu, Yang; Du, Yang; Fang, Ting; Chen, Guoliang
Graphical abstract: Highlights: Iridium can catalyzed intramolecular CN and CO/S cross-coupling reactions. Benzoazole derivatives are readily available using this method. Iridium catalyst can be effective with just 1 mol% catalyst loading. Iridium performs better with low reactivity substrates than Cu or Pd. One drug was prepared using this method. Abstract: The irdium-catalyzed intramolecular arylcarbon-hetero cross-coupling reactions with o -haloarylamides or o -haloarylamidine have been effectively achieved using KOAc and just 1 mol% catalyst. The [Ir(cod)Cl]2 was proved to be more potential for smoothly assembling functional structures benzimidazoles, benzoxazoles and benzothiazoles, which was superior to Cu- and Pd-catalyzed systems. Simultaneously, a concise and efficient synthesis of tafamidis was developed in 5-g scale.